Involvement of Polyamine Oxidase-Produced Hydrogen Peroxide during Coleorhiza-Limited Germination of Rice Seeds - Chen, Bing-Xian; Li, Wen-Yan; Gao, Yin-Tao; Chen, Zhong-Jian; Zhang, Wei-Na; Liu, Qin-Jian; Chen, Zhuang (Frontiers in Plant Science, 2016)
Seed germination is a complicated biological process that requires regulated enzymatic and non-enzymatic reactions. The action of polyamine oxidase (PAO) produces hydrogen peroxide (H2O2), which promotes dicot seed germination. However, whether and, if so, how PAOs regulate monocot seed germination via H2O2 production is unclear. Herein, we report that the coleorhiza is the main physical barrier to radicle protrusion during germination of rice seed (a monocot seed) and that it does so in a manner similar to that of dicot seed micropylar endosperm. We found that H2O2 specifically and steadily accumulated in the coleorhizae and radicles of germinating rice seeds and was accompanied by increased PAO activity as the germination percentage increased. These physiological indexes were strongly decreased in number by guazatine, a PAO inhibitor. We also identified 11 PAO homologs (OsPAO1–11) in the rice genome, which could be classified into four subfamilies (I, IIa, IIb, and III). The OsPAO genes in subfamilies I, IIa, and IIb (OsPAO1–7) encode PAOs, whereas those in subfamily III (OsPAO8–11) encode histone lysine-specific demethylases. In silico–characterized expression profiles of OsPAO1–7 and those determined by qPCR revealed that OsPAO5 is markedly upregulated in imbibed seeds compared with dry seeds and that its transcript accumulated to a higher level in embryos than in the endosperm. Moreover, its transcriptional abundance increased gradually during seed germination in water and was inhibited by 5 mM guazatine. Taken together, these results suggest that PAO-generated H2O2 is involved in coleorhiza-limited rice seed germination and that OsPAO5 expression accounts for most PAO expression and activity during rice seed germination. These findings should facilitate further study of PAOs and provide valuable information for functional validation of these proteins during seed germination of monocot cereals.